THE USE OF CODE-SWITCHING BY ENGLISH TEACHERS IN FOREIGN LANGUAGE CLASSROOM - Ulfah, Nur Maria; Tsuraya, Annisa Shofa; Risal, Risal (English Language, Linguistics, and Culture International Journal, 2021)
This research aimed at finding out; (1) types of code-switching used by English teachers in foreign language classroom, (2) the factors triggering the English teachers to use code-switching in the classroom, and (3) the functions of code-switching used by English teachers in the classroom. This research was conducted through descriptive qualitative method. The samples of the research consisted of 6 English teachers. In order to gather the data, the researcher used three instruments of research, they were: classroom observation, recorder, and interview. The types of code-switching appearing in the classroom were observed based on the theory proposed by Poplack, while the factors triggering the teachers to use code-switching in the classroom proposed by Holmes‟ theory, and the functions of code-switching in the classroom were perceived through the functions proposed by Sert. Moreover, to interpret the data gathered, the researcher analyzed them through three steps of analysis by using mode from Miles and Huberman, they were: data reduction, data description, and data classification. The findings indicated that the types of code-switching were simply found in three types: (a) inter-sentential code-switching (without inserting new information and which inserts new information), (b) intra-sentential code- switching (translation or word/phrase substitution within a sentence), and (d) tag- switching (interactional fillers code-switching). The factors triggering the English teachers to use code-switching in the classroom was found for four reasons, they are: (a) rhetoric reason, (b) differences of status and formalities, (c) quote other statements or proverbs, and (d) lack of vocabulary. And other factors gather from the classroom setting are: (a) the students‟ ability in English are not the same, (b) code-switching emerges automatically or unconsciously, and (c) helping the students to share their ideas. Moreover, the functions of code-switching used by English teachers in the classroom were found for three functions; (a) topic switch, (b) affective function, and (c) repetitive function.